Investigating The Quality of The Clinical Learning Environment Based on The DREEM Model In Akbar Educational Hospital of Mashhad in 1400 - majid Khadem-Rezaiyan; aylor Avazzadeh; roya Vatankhah; hamidreza Kianifar; nafiseh Pourbadakhshan (Babol University of Medical Sciences, 2023)
Background and Objective: The learning environment is a behavioral determinant and the student's understanding of the environment is very important in learning and clinical education. The DREEM model is used as a diagnostic tool to identify the difference between the real environment and the desired environment. The purpose of this study is to investigate the opinions of medical students and their professors about the quality of the clinical learning environment. Methods: This cross-sectional study was done between 2021 and 2022 and the views of 233 medical students (assistants, interns and externs) and faculty members was gathered using the DREEM questionnaire in five areas of student perception of learning, professors, educational atmosphere, scientific ability, and social conditions. SPSS 27 was used to analyze the data.    Findings: Mean score of the clinical education status in the main wards of the educational center was 120.00±23.07 of 200 Mean score of students' perceptions of learning was 26.85±7.22, perceptions of teachers (28.49±4.53), academic self-perception (19.06±4.70), perception of the academic atmosphere (29.54±6.37), and social self-perception (16.06±4.29).Assistant professors and associate professors considered the condition of the clinical learning environment of the hospital more favorable than interns (0.006 and 0.002, respectively) and externs (0.019 and 0.006, respectively). Conclusion: Educational environment of Akbar hospital was evaluated as favorable in all areas. This shows the high attention of professors to the principles of educational design and the creation of appropriate educational space. However, to further improve quality, the DREEM model can be used to monitor and measure modification and change in clinical education program.